Synoptic and climatological controls of particulate matter pollution in a Southern Hemisphere coastal city. (20th February 2012) - Appelhans, Tim; Sturman, Andrew; Zawar‐Reza, Peyman
Abstract A complex interaction of local meteorology and source characteristics regularly leads to nocturnal smog events during winter in Christchurch, New Zealand. The main focus of this article is on improving understanding of the relationship between atmospheric processes operating at a range of scales that leads to poor air quality in such urban environments. This research therefore aims to provide a quantitative analysis of atmospheric influences on particulate matter pollution in Christchurch across a wide range of spatial and temporal scales, from local to hemispheric and daily to interannual. The probability of exceeding the National Environmental Standard for PM10 for a range of local atmospheric conditions is calculated using the classification and regression trees technique, and links between these probabilities, local meteorology and synoptic weather situations are established. The effect of the transition between synoptic types on local air quality is also examined, and the progression of anticyclones across the country is identified to be the dominant synoptic control mechanism. It is shown that variation in latitudinal location of the path of anticyclones over New Zealand influences the predicted exceedance probability. On interdecadal and hemispheric scales, it is found that the particular combination of local and synoptic atmospheric conditions that favours air quality degradation shows a reoccurring pattern of frequency maxima (and minima) with a periodicity of approximately 14‐16 years. In relation to the identified interdecadal variability of synoptic circulation, a close relationship to Southern Hemisphere pressure anomalies at high latitudes is revealed. The results of this research show that, in addition to daily weather variation, air quality in Christchurch is influenced by longer‐term climatic processes that operate on interannual hemispheric scales with the implication that, in general, air pollution potential can also be expected to vary on a periodic interdecadal time scale. Copyright © 2012 Royal Meteorological Society